Alkaloids from Litsea elliptibacea (Lauraccae)Â° - Chuah, C.H. '; Lee', K.H.; Goh, S.H.; Goh, S.H. (Malaysian Journal of Science, 1999)
(+)-N-methylactinodaphnine, (+)-actinodaphine, (+)-N-methyllaurotetanine, (+)-boldine, (+)- norboldine and (+)-reticuline were isolated from the stem-bark of Litsea elliptibacea. The structures of the alkaloids were deduced from their spectral data.